DECOMPENSATED DIABETES MELLITUS BINOMIAL - EMPHYSEMATOUS PYELONEPHRITIS AND PERIODONTAL DISEASE - Cristiana-Elena Vlad; Liliana Foia; Cosmin-Alexandru Agache; Ștefan-Adrian Strungaru; Vasilica Toma; Amelia Surdu; Ancuța Goriuc; Laura Florea (Romanian Society of Oral Rehabilitation, 2018)
Introduction: Periodontal disease and emphysematous pyelonephritis, 2 independent pathologies, were determined by ineffective blood glucose monitoring. Emphysematous pyelonephritis is commonly associated with diabetes, especially in women, with impaired immune system and urinary tract obstruction, which subsequently over-infects. Predisposing factors are: diabetes mellitus, end stage renal disease, immunosuppression, urinary tract obstruction, and rarely polycystic kidney disease. Periodontitis is an inflammatory disease of the gum and deep periodontal tissues, preceded and accompanied by gingivitis. The primary etiology of the periodontal lesion is anaerobic, gram-negative bacteria: Aggregatibacter actinomycetemcomitans, Tannerella forsythensis, Porphyromonas gingivalis, Prevotella intermedia, Fusobacterium nucleatum, Campylobacter rectus, and Treponema denticola. Clinical-case: A 71-year-old patient known for complex pathology addressed our clinic due to lower urinary tract symptoms (pollakiuria, dysuria). The clinical examination reports: overall influenced condition, afebrile, at the level of the oral cavity: generalized inflammation, gingival recession, plaque deposits, small bleeding, swelling and inflammation, abnormal gingival anatomy owing to tissue destruction. Chemistry panel reveals inflammatory syndrome, metabolic acidosis, hyperglycemia, pathological urinalysis (leukocyturia, hematuria, microbial flora, ketone bodies), and urine culture positive for E. coli, multidrug resistant (sensitive to Meropenem, Linezolid). The medical imaging (abdominal ultrasound, abdominopelvic CT scan with contrast medium) show lesions associated with emphysematous pyelonephritis. Corroborating the anamnestic, clinical and paraclinical data, the patient was diagnosed with right emphysematous pyelonephritis, periodontal disease and diabetic ketoacidosis. Conclusion: After early initiation of the maximum therapeutic regimen (antibiotic therapy, double J stent and percutaneous nephrostomy), the patient presented a worsening in dynamic of the general condition, chemistry panel and imaging aspect (disorganization of the renal architecture, gas bubbles) the reason why radical nephrectomy was required. Clinical-biological post-operative evolution was good. Adjustment of glycemic values ​​in diabetic patients result in improvement of the periodontal disease symptomatology.